Cathepsin K inhibition renders equine bone marrow nucleated cells hypo-responsive to LPS and unmethylated CpG stimulation in vitro. (April 2016) - Hussein, Hayam; Boyaka, Prosper; Dulin, Jennifer; Bertone, Alicia
Highlights: Cathepsin K is an important enzyme regulating bone degradation and the immune response. We investigated the effect of Cathepsin K inhibition on equine bone marrow nucleated cells (BMNCs) immune response. Cathepsin K inhibition promoted BMNCs viability and reduced cell apoptosis. Cathepsin K inhibition significantly decreased cytokine production of BMNCs. Cathepsin K inhibition altered different BMNCs surface markers and MHC II molecule expression. Abstract: Cathepsin K (CatK) is an important enzyme regulating bone degradation and has been shown to contribute to the immune response. We have studied two inflammatory models in equine bone marrow nucleated cells (BMNCs); the LPS and the unmethylated CpG stimulation with the following objectives to: 1.determine whether CatK inhibition will alter the cytokine secretion by stimulated BMNCs; specifically IL-1β, IL-6, and TNF-α, and 2.determine the changes in BMNCs surface markers' expression and MHC II molecule under CatK inhibition. Cathepsin K inhibition promoted BMNCs viability and reduced cell apoptosis. Moreover, CatK inhibition significantly decreased cytokine secretion of either naïve or stimulated BMNCs, and altered their MHC II molecule expression. In conclusion, CatK inhibition in horses did affect BMNCs other than mature osteoclasts rendering them hypo-responsive to both TLR4- and TLR9-induced inflammation, predicting a proteolytic activity for CatK within the MyD88 pathway and/or the following proteolytic events required for the cytokines secretion.